Sub-millisecond closed-loop feedback stimulation between arbitrary sets of individual neurons - Müller, Jan; Bakkum, Douglas J.; Hierlemann, Andreas (Frontiers in Neural Circuits, 2013)
We present a system to artificially correlate the spike timing between sets of arbitrary neurons that was interfaced to a complementary metal oxide semiconductor (CMOS) high‐density microelectrode array (MEA). The system features a novel reprogrammable and flexible event engine unit to detect arbitrary spatiotemporal patterns of recorded action potentials and is capable of delivering sub‐millisecond closed‐loop feedback of electrical stimulation upon trigger events in real‐time. The relative timing between action potentials of individual neurons as well as the temporal pattern among multiple neurons, or neuronal assemblies, is considered an important factor governing memory and learning in the brain. Artificially changing timings between arbitrary sets of spiking neurons with our system could provide a “knob” to tune information processing in the network.